CEO's temporal orientation : the contexts of CEO retirement and CEO succession - Thosuwanchot, Nongnapat (Nanyang Technological University, 2018)
Issues related to time horizon have received increasing attention due to the perceived reluctance of executives to engage in long horizon investments. Temporal orientation is the relative importance of the issues in short versus long time horizon that individuals pay attention to. Although temporal orientation is instrumental to firm survival, there are still limited theoretical frameworks that explore temporal orientation of firms’ executives. Due to the limited attention on the antecedents of temporal orientation, especially at the individual level, this thesis examines temporal orientation of the CEOs by using content analysis of CEOs’ letters to shareholders. I first examine CEOs’ temporal orientation in the context of CEO retirement. I propose that retiring CEOs become more short-term oriented as they are more motivated to engage in opportunistic behaviors towards opportunities with shorter term payoff. By incorporating prospect theory with agency theory, I also examine different components of major CEOs’ incentives, including cash compensation, stock options and equity ownership, as boundary conditions that can alter retiring CEOs’ temporal orientation. In particular, prospect theory helps to modify agency theory’s assumptions to consider compensation risk associated with different elements of stock-based incentives. I test the hypotheses on a sample of firms listed in the S&P 500 index from 2009 to 2013, and the findings support the theoretical arguments. I further examine CEOs’ temporal orientation in the context of CEO succession. By drawing on impression management theory, I propose that relay successors are more short-term oriented than nonrelay inside successors and outside successors. Moreover, I examine several boundary conditions that further accentuate or attenuate the extent that the relay successor is motivated to engage in impression management and thus become more short-term oriented. These boundary conditions include performance below historical and social aspirations and narcissistic personality of the successors. In addition, narcissistic personality of relay successors is expected to influence how they interpret performance below two different types of aspirations, which in turn impact their temporal orientation. I test these hypotheses on a sample of CEO successions covering the years 2008-2016 of firms listed in the S&P 500 index. The results largely support these theoretical arguments. Overall, my research contributes to our understanding on the antecedents of temporal orientation at the individual level of analysis. In the context of CEO retirement, this study draws on prospect theory to highlight consistent prediction as well as contradiction between agency theory and prospect theory. This resolves inconsistent findings regarding the roles of stock-based compensation in influencing temporal orientation. By examining the roles of CEO compensation in more fine-grained elements, the results offer insights for implementing appropriate compensation plans for the CEOs approaching retirement. In the context of CEO succession, this study highlights different impacts of performance below historical and social aspirations on CEO’s temporal orientation, where the CEO’s personality also plays an important role. An important practical implication is to encourage the board of directors to pay more attention in monitoring the relay successor’s short-term decisions that may be detrimental to the firm.